MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) SEBAGAI UPAYA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Nurhanipah, Nurhanipah; Huda, Ade Nailul; Sari, Anggie Septia; Subarna, Intan Caroline; Hanifah, Nuriah; Saputra, Riyan; Khairunnisa, Arin (SINERGI : Jurnal Riset Ilmiah, 2025)
This study seeks to evaluate the efficacy of the Contextual Teaching and Learning (CTL) paradigm in enhancing student learning outcomes via a systematic literature review method.  Data was gathered from five research publications published between 2019 and 2024, which explicitly addressed the implementation of CTL models across various levels and subjects.  The analytical results indicate that the implementation of CTL significantly enhances student learning outcomes across cognitive, emotional, and psychomotor domains.  Moreover, CTL has been demonstrated to enhance student engagement and desire for learning, while also fostering the development of critical thinking and problem-solving abilities.  This technique entails connecting subject matter to real-life contexts, utilizing instructional resources, and fostering an interactive and collaborative learning environment.  Nonetheless, the efficacy of CTL implementation is significantly affected by the teacher's preparedness in developing and implementing contextual learning.  consequence, CTL can be used as an alternative strategy in learning that not only focuses on academic outcomes, but also on strengthening character and competence.